Analisa Pembebanan pada Bilah Pengaduk dan Poros Utama pada Mesin Pencampur Pupuk Majemuk dengan Sofware SOLIDWORK - Suherman, Suherman; Abdullah, Ilmi; Suharlan, Didy; Sai'in, Ali; Harahap, Muchsin (Mechanical Engineering Department - Semarang State Polytechnic, 2024)
A compound fertilizer mixing machine (mixer) is a type of machine used to produce compound fertilizer. This fertilizer consists of a mixture of humus fertilizer, animal manure and humus soil. This machine is very important in its use as a mixer of different types of fertilizer ingredients, so as to produce a homogeneous mixture. The aim of this research is to design a fertilizer mixing machine that can be used by small and medium industries and farmer groups. In this design, consider the factors that influence the strength of the main components, such as the drive shaft, mixing blade, belt transmission system, machine frame, etc. This research was carried out in three stages, namely the load simulation stage on the drive shaft and stirrer blade to determine the safety factor. The second stage is calculations in the design of the main components of the machine. In the final stage, the process of making the machine and testing is carried out. The design of this machine was simulated using SOLIDWORK 20 software. The simulation results using SOLIDWORK showed a minimum FOS (Factor of Safety) value of 2.98 on the stirrer blade and the main shaft had met the safety factor. The test results of this fertilizer mixing machine have a capacity of 950 kg/hour.